Композиційні кластерні структури мобільних генетичних елементів у інтронах гена MGMT як джерело регуляторних послідовностей - Підпала, О.В.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2014)
Aims. It was carried out analysis of the composite cluster structures MGE in intron 2 and 3 of human MGMT gene for the sequences homologous to binding sites of transcription factors. Methods. Searching and identifying MGE was realised by using CENSOR (http://www.girinst.org). Functional sites were defined by program TFSEARCH: Searching Transcription Factor Binding Sites (ver 1.3) (http://www.cbrc.jp/research/db/TFSEARCH.html). Results. Composite clusteres in the introns 2 and 3 of human MGMT gene consist of Alu-repeat and fragments of LINE-elements. Both sequences are enriched promotorspecific elements including the TATA box, AP-1, Sp1, SREBP-1, Oct-1, HSF2 and others. Exept that fragments of the LINE-elements have sites binding for the glucocorticoid receptor and orphan hormone nuclear receptor. Conclusions. The obtained results allow to consider analyzed intron clusters of MGE as potential alternative promoters.